Transformation of Village Government Management Post-Efficiency Towards a Sustainable Governance Model - Nursan Safitri; Resky Faradibah Suhab; Sucianti Sukiana Sari (Journal of Public Representative and Society Provision, 2026)
This study aims to analyze the impact of budget efficiency policies on village governance and formulate a sustainable management model amidst fiscal constraints. A qualitative approach with a single case study design was used in Rumpa Village, Mapilli District, Polewali Mandar Regency. Data were collected through in-depth interviews with ten key informants, participant observation, and focus group discussions, then analyzed using thematic analysis and source triangulation techniques. The results show that budget efficiency policies require organizational transformation through the reduction of non-structural staff, cross-functional task allocation, and reprioritization of village programs to basic services and mandatory infrastructure. However, this policy also triggers adaptive and innovative management practices such as micro-data-based planning for neighborhood units (RT/RW), digitization of basic administration for service efficiency, the establishment of village alms as a local financing innovation, and the optimization of mutual cooperation (gotong royong) that can reduce development costs by up to 50%. Based on the findings, this study formulates a Sustainable Village Governance Model (EAP Model) that includes five main components: data-driven efficiency, institutional adaptation, multi-stakeholder participation, local financing innovation, and open accountability. This model integrates New Public Management theory and Putnam's social capital to support adaptive, innovative, participatory, and sustainable village governance. This study concludes that fiscal constraints are not an obstacle to village development if mitigated through innovative organizational transformation and optimal community participation, thus supporting the vision of an inclusive and independent Golden Indonesia 2045.